Trends towards Coordination between Grain Production and Economic Development in China - Kun Xie; Mingjun Ding; Jianrong Zhang; Liwen Chen (Agriculture, 2021)
Accurately understanding the relationship between grain production and economic development is of great practical significance for ensuring national food security and coordinating inter-regional economic development. Using 2012 counties as research units, we analyzed the spatial coordination between grain production and economic development in China using the coupling of grain and economy (CGE) index, as well as the curve of gravity center and thematic map series methods based on statistical data from counties between 2000–2017. The results showed that: (1) Grain production was weakly coordinated with the economic development in China; but this coordination was enhanced. (2) China’s conversion between various types of grain production and economic development mainly occurred in the central and western regions, which are characterized by a much higher grain agglomeration level than the economic agglomeration level. (3) The northeastern region was prone to the grain agglomeration, the central and western regions were characterized by a grain-economy balance and the eastern region was dominated by economic agglomeration. (4) The increase of China’s CGE gradually increased from the southwest to northeast. Therefore, we proposed that the government should pay more attention to grain circulation in the eastern region and main grain-producing areas in central region should develop an accurate benefit compensation system, support leading grain processing enterprises and implement cultivated land protection policies in order to ensure national food security.